Translation of the German Federal Constitutional Court’s Plane Hijack Verdict and Analysis of the Relationship Between Human Rights and Terrorism Based on This Verdict - Berk Cem Tatar (İstanbul Hukuk Mecmuası)
When compared, isthe life of 10,000 people more important than the lives of 150? Ifso, can human life be viewed only as a quantitative number? Before answering the question, it should be considered that is it possible to look only at numbers without looking at people’s backgrounds? The German Federal Constitutional Court discussed this situation in detail in its verdict examined in this study. For this reason, in this study, a critical verdict in this regard was translated into Turkish, and then an analysis was written in terms of the method of reaching the result in the decision. During the analysis in question, philosophical approaches were made that the right to life cannot be objectified and that human beings can only be the subject of a right. In addition, the methods used by the German Constitutional Court during the examination of the case in question were discussed. In this case, which arose out of an enacted law, the Court did not use only the legal background while examining it. Members of Parliament with different opinions were given the opportunity to present their views on the case. In addition, not only the deputies submitted their opinions, but also the German Armed Forces Association, the Pilots’ Association, and the Independent Flight Attendant Organisation submitted written opinions. With this approach, the differences in the examination of a case before the Turkish Constitutional Court are also mentioned.